Outbreak of persistent cutaneous abscesses due to Mycobacterium chelonae after mesotherapy sessions, Lima, Peru Surto de abscessos cutâneos persistentes por Mycobacterium chelonae pós-mesoterapia, Lima, Peru - César V Munayco; Carlos G Grijalva; Dante R Culqui; José L Bolarte; Luis A Suárez-Ognio; Neyda Quispe; Roger Calderon; Luis Ascencios; Manuel Del Solar; Martín Salomón; Francisco Bravo; Eduardo Gotuzzo (Universidade de São Paulo, 2008)
Outbreaks of rapidly growing mycobacteria have been occasionally described. The article reports an outbreak of cutaneous abscesses due to Mycobacterium chelonae following mesotherapy in Lima, Peru. From December 2004 through January 2005, 35 subjects who had participated in mesotherapy training sessions presented with persistent cutaneous abscesses. Thirteen (37%) of these suspected cases consented to underwent clinical examination. Skin punch-biopsies were collected from suspicious lesions and substances injected during mesotherapy were analyzed. Suspected cases were mainly young women and lesions included subcutaneous nodules, abscesses and ulcers. Mycobacterium chelonae was isolated from four patients and from a procaine vial. In conclusion, it is important to consider mesotherapy as a potential source of rapidly growing mycobacteria infections. Surtos de micobactérias de crescimento rápido têm sido relatados ocasionalmente. O estudo relata um surto de abscessos cutâneos por Mycobacterium chelonae após sessões de mesoterapia em Lima, Peru. De dezembro de 2004 a janeiro de 2005, 35 pessoas que haviam passado por sessões de mesoterapia apresentaram esses abscessos cutâneos. Treze (37%) desses casos suspeitos concordaram em realizar exames clínicos. Foram realizadas biópsias de punção de pele de lesões suspeitas e examinadas substâncias injetadas durante a mesoterapia. Os casos suspeitos eram predominantemente mulheres jovens e as lesões incluíram nódulos subcutâneos, abscessos e úlceras. Mycobacterium chelonae foi isolada de quatro pacientes e de um frasco de procaína. Em conclusão, é importante considerar a mesoterapia como fonte potencial de infecções de micobactérias de crescimento rápido.